2015
DOI: 10.1111/ddi.12315
|View full text |Cite
|
Sign up to set email alerts
|

Across‐ecoregion analysis suggests a hierarchy of ecological filters that regulate recruitment of a globally invasive fish

Abstract: Aim Even successful invaders are abundant only in a fraction of locales they inhabit. One of the main challenges in invasion ecology is explaining processes that drive these patterns. We investigated recruitment of a globally invasive fish, common carp (Cyprinus carpio), across three ecoregions to determine the role of environmental characteristics, predatory communities and propagule pressure on the invasion process at coarse and fine spatial scales. Location Lakes across Northern Forest, Temperate Forest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Decline in plant diversity and cover also hinders fundamental ecosystem functions such as maintaining water clarity, reducing erosion or sequestering nutrients (Engelhardt & Ritchie, ; Haas et al ., ). The abundance of carp tends to be highest in hypereutrophic lakes in agricultural and urban areas (Kulhanek et al ., ,b; Bajer et al ., ). Although site‐specific studies have shown the effects of carp on aquatic ecosystems (Vilizzi et al ., ), it has not been demonstrated whether common carp can be prevalent and important enough to cause sweeping declines in diversity and ecosystem function across entire geographic regions.…”
Section: Introductionmentioning
confidence: 97%
“…Decline in plant diversity and cover also hinders fundamental ecosystem functions such as maintaining water clarity, reducing erosion or sequestering nutrients (Engelhardt & Ritchie, ; Haas et al ., ). The abundance of carp tends to be highest in hypereutrophic lakes in agricultural and urban areas (Kulhanek et al ., ,b; Bajer et al ., ). Although site‐specific studies have shown the effects of carp on aquatic ecosystems (Vilizzi et al ., ), it has not been demonstrated whether common carp can be prevalent and important enough to cause sweeping declines in diversity and ecosystem function across entire geographic regions.…”
Section: Introductionmentioning
confidence: 97%
“…Unintentionally introduced species can be detrimental to intentionally introduced fishes through predation or competitive interactions for shared prey resources (Gardunio et al 2011;Guy et al 2011). However, even intentionally introduced species may not be successfully established Williamson and Fitter 1996;Bajer et al 2015). Successful introductions, whether intentional or not, may initiate novel predator-prey interactions Romare and Hansson 2003;Schoen et al 2012), alter trophic structure (Reissig et al 2006;Skov et al 2010;Ellis et al 2011), or increase the potential for competition (Tyus and Saunders 2000;Tronstad 2008;Winters and Budy 2015).…”
mentioning
confidence: 99%
“…As discussed above, this hinders the identification of hierarchical structures in the controls of invasion (e.g. biotic interactions filtering out non‐natives at the local community scale, and environmental filters preventing or allowing them at the regional scale; Bajer et al ., ). Nevertheless, because spatial aggregation decreases variance, patterns that can be observed using our approach should be at least as clear using finer‐scale data.…”
Section: Discussionmentioning
confidence: 99%
“…Bullfrog tadpoles are also mostly unpalatable to predatory fishes (Kruse & Francis, ), but they are, however, vulnerable to predation by salamanders and dragonfly larvae (Werner & McPeek, ), and adult and juvenile bullfrogs are also frequently preyed by large vertebrates (Lannoo, ). Recent evidence suggests that environmental controls and predation pressure can interact and influence invasive fish at hierarchical spatial scales (Bajer et al ., ). Although this possibility could not be addressed in our case due to the nature of our data, increasing availability of large‐scale, spatially explicit databases should open opportunities to test, in the near future, if similar hierarchical filters exist in amphibian communities.…”
Section: Discussionmentioning
confidence: 99%